In vitro study of the effect of three commercial solvents on gutta-percha cones used for the cold and thermoplastic technique - Saavedra Gonzales, Paul Josep (2022)
The objective of this research was to compare the solvent action of orange oil, eucalyptol and experimental lemongrass oil on gutta-percha cones for cold technique and thermoplastic technique. Methodology: The sample consisted of 80 gutta-percha cones No. 80 Endomedic and F3 ProTaper Universal. The cones were divided into 4 groups (n = 20) according to the type of solvent, and each one was divided into two subgroups (n = 10) according to the exposure time (5 min and 10 min). The cones were immersed in the respective solvent for 5 or 10 minutes. Then, they were washed with 5 ml of alcohol for 5 minutes and rinsed with water. Finally, after drying at room temperature for one hour, the solvent action was recorded in grams (g) of weight loss. The results were analyzed and compared using Tukey's test (p<0.05). Results: The Endomedic cone exposed for 5 min to eucalyptol obtained the lowest average weight (0.0625 ± 0.0009 g), followed by Lemongrass oil (0.0629 ± 0.0003 g) and orange oil (0.0629 ± 0.0010 g), although not a significant difference (p > 0.05) was found between each one. Conclusion: The experimental solvent of Lemongrass, eucalyptol and orange oil presented a similar solvent effect on the guta-percha cone for cold and thermoplastic technique. At a clinical level, the three solvents studied could be used in endodontic retreatment as alternative solutions with a similar solvent effect.